Effectiveness of percutaneous tibial nerve stimulation in managing refractory constipation. (January 2017) - Kumar, L.; Liwanag, J.; Athanasakos, E.; Raeburn, A.; Zarate‐Lopez, N.; Emmanuel, A. V.
Abstract: Aim: Chronic constipation can be aetiopathogenically classified into slow transit constipation (STC), rectal evacuation difficulty (RED) or a combination (BOTH). Although the efficacy of percutaneous tibial nerve stimulation (PTNS) in faecal incontinence has been well proved, a current literature search identifies only one study which assessed its effect on constipation. We aimed to evaluate the effectiveness of PTNS in patients with different causes of constipation. Method: Thirty‐four patients [30 women, median age 50 (20−79) years] with constipation who had previously failed maximal laxative and biofeedback therapy participated in the study. All patients underwent a baseline radio‐opaque marker transit study and anorectal physiology examination. All had 12 sessions of PTNS of 30 min per session. A fall in the Wexner constipation score to ≤15 or by ≥5 points was taken as the primary outcome. Secondary outcomes included the results of pre‐ and post‐ PTNS transit and anorectal physiology studies. Results: Eleven patients had STC, 14 had RED and nine had BOTH. A response was seen in four patients (1/11 STC, 2/14 RED and 1/9 BOTH). Comparing pre‐ and post‐ PTNS, there was no significant change in the mean Wexner score ( P  =   0.10). There was no change in colonic transit time among the whole population ( P  =   0.56) or among those with STC ( P  =   0.47). There was no improvement in balloon expulsion in the whole group ( P  =   0.73) or in patients with RED ( P  =   0.69). Conclusion: PTNS is of no benefit to patients with constipation, whatever aetiopathogenic mechanism is responsible for the symptoms.